Журнал "Мектеп ве аиле" как тип издания - Юксель, Г.З. (Культура народов Причерноморья, 2014)
В статье проводится структурно-типологической и проблемно-тематический анализ издания "Мектеп ве айле" ("Школа и семья"), выходивший в Румынии в 1915-1916 гг., определена аудиторная направленность, авторский состав, жанровая структура издания, дана оценка роли издания в жизни региона и социума, раскрыта основная тематика публикаций, которая было определена целями и задачами, а также потребностями читательской аудитории. У статті надається структурно-типологічної і проблемно-тематичний аналіз видання "Мектеп ве айле" ("Школа і сім'я"), який друкувався у Румунії в 1915-1916 рр., визначена аудиторна спрямованість, авторський склад, жанрова палітра видання, дана оцінка ролі видання у житті регіону та соціуму, розкрито основна тематика публікацій, яка була визначена метою та завданнями, а також потребами читацької аудиторії. In investigating of the history of national media, special focus is paid for the media of Crimean Tatar diaspora, founded by ethnic Crimean Tatars, living mostly in Turkey, Romania and Bulgaria. The purpose of the scientific work is to form typological model of “Mektep and Aile” (“School and Family”) magazine, one of the most important edition of Crimean Tatar diaspora, that was published in 1915-1916 in the city of Dobruja in Romania. The article investigates typological characteristics of the Mektep ve Aile" magazine, defines formative, basic and additional features and describes the thematic orientation of the edition. Structure typological analysis of “Mektep ve Aile” magazine allows suggesting that the magazine was social political edition, oriented to Crimean Tatar diaspora in Romania. The social political orientation of authors and editors together with topical themes, raised in the magazine, predetermined the contents of the edition and genre originality. The “Mektep ve Aile” has played a great role in describing the social situation in the region, and promoted the discussion of actual problems of Crimean Tatar diaspora. It became a kind of spiritual center of communication, debate and a platform for creative endeavors of scientific and literary intellectuals in the region.